Lim (as x --> 1) of (x^4 - 3x^3 + 2) / (x^3 - 5x^2 + 3x + 1)
Notice that when x = 1, both the numerator and the denominator equal zero. Therefore, (x - 1) must be a factor of both terms.
Dividing out this factor in both terms gives :
(x^3 - 2x^2 - 2x - 2) / (x^2 - 4x -1)
Notice now, that when x = 1, both the numerator and the denominator do not equal zero. Therefore, there are no more factors in either term that equals (x - 1).
So now we can let x = 1 and substitute. This gives :
[1^3 - 2(1^2) - 2(1) - 2] / [1^2 - 4(1) - 1]
= -5 / -4
= 5 / 4, which is the limit as x --> 1.
2006-11-11 18:45:21
·
answer #1
·
answered by falzoon 7
·
0⤊
1⤋
limit=1-3+2/1-5+3+1=0/0
applying L Hospitals rule
limit=x>1 4x^3-9x^2/3x^2-10x+3
=1-9/3-10+3
=-8/-4=2 (answer)
Lim (as x --> 1) of (x^4 - 3x^3 + 2) / (x^3 - 5x^2 + 3x + 1)
Notice that when x = 1, both the numerator and the denominator equal zero. Therefore, (x - 1) must be a factor of both terms.
Dividing out this factor in both terms gives :
(x^3 - 2x^2 - 2x - 2) / (x^2 - 4x -1)
Notice now, that when x = 1, both the numerator and the denominator do not equal zero. Therefore, there are no more factors in either term that equals (x - 1).
So now we can let x = 1 and substitute. This gives :
[1^3 - 2(1^2) - 2(1) - 2] / [1^2 - 4(1) - 1]
= -5 / -4
= 5 / 4, which is the limit as x --> 1
2006-11-12 03:23:06
·
answer #2
·
answered by shriya 2
·
0⤊
0⤋
lim x (x ^4 - 3x ^3 + 2)/(x ^3 - 5x ^2 + 3x + 1)
x --->1
This limit is of form 0/0 on substitution(x=1). Therefore you can directly apply L' Hospital's rule.
=>lim x (x ^4 - 3x ^3 + 2)/(x ^3 - 5x ^2 + 3x + 1)
x --->1
=>lim (5x ^4 - 12x ^3 + 2)/(3x ^2 - 10x + 3x)
x --->1
substituting x=1 =>(5-12+2)/(3-10+3)=-5/-4= 5/4
2006-11-12 17:06:47
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2
2006-11-11 17:47:28
·
answer #4
·
answered by satyamrajput_0 2
·
0⤊
3⤋
Simply substitute 1 for x. There are no parts to the equation you've presented where you have a zero in the denominator so
x^4=1
3x^3=3
2/x^3=2
5x^2=5
3x=3
so the equation is 1-3+2-5+3+1= -1
2006-11-11 18:20:14
·
answer #5
·
answered by cibman 2
·
0⤊
0⤋
Yes, the above statements are right, use L'Hopital's Rule (I get 5/4), but I just wanted to add that it's always a good idea to include parenthesis when typing a function such as been written. (I assume, based on the context of the problem, I deduced that you meant (x ^4 - 3x ^3 + 2) /( x ^3 - 5x ^2 + 3x + 1), since otherwise the problem is trivial)
Just a friendly little tip to help make things a bit clearer.
2006-11-11 18:20:39
·
answer #6
·
answered by smartjock256 2
·
0⤊
1⤋
limit=1-3+2/1-5+3+1=0/0
applying L Hospitals rule
limit=x>1 4x^3-9x^2/3x^2-10x+3
=1-9/3-10+3
=-8/-4=2 (answer)
2006-11-11 17:38:57
·
answer #7
·
answered by raj 7
·
0⤊
2⤋
Yes, use L'Hopital's Rule. However, i got 5/4.
And yes, parenthesis do help. I did this problem assuming that it was a fraction. If so, then it is 5/4
2006-11-11 18:20:04
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
ahdjashda i cant make sure it out yet youve were given me questioning! haha im confident you dont care yet this jogs my memory of that riddle: its more effective than god extra evil than the devil the adverse have it the wealthy favor it and in case you eat it you die everybody's heard that... yet when your friends havent you may shoot it decrease back at em haha.. playstation ..? are you able to wager the answer...
2016-11-29 01:37:53
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
divide the numerator by (x-1) and denominator by (x-1)
after that replace x by 1 and you will get your answer.
2006-11-11 17:36:04
·
answer #10
·
answered by Pegasus 3
·
0⤊
1⤋